2008
DOI: 10.1007/s11294-008-9196-1
|View full text |Cite
|
Sign up to set email alerts
|

The Value Relevance of Earnings and Nonearnings Information in Regulated and Deregulated Markets: The Case of the Airline Industry

Abstract: Regulated markets, Valuation relevance, Earnings and nonearnings information, Airline industry,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“… POSTREG: The variable of interest post-regulation (POSTREG) is measured by a binary variable which takes value of 1 during the period after the change of regulation and value 0 for the period before – the change of regulation (Cohen et al , 2005, 2008; Lobo and Zhou, 2006, 2009; Naser et al , 2002; El-Gazzar et al , 2009). Board of directors : Three measurements will be considered in our study, namely, size of the board (BSIZE), measured by the number of directors on the board of directors (Yermack, 1996; Adams and Mehran, 2002; Klein, 2002b); the independent director (OUTSD), several researchers have addressed the influence of the percentage of outside director on the board of directors and they found a positive association between the independence of directors and the level of financial disclosure (Bhagat and Black, 1999); and audit committee (ACOM), measured by a dummy variable equal to 1 if the company has an internal audit committee and 0 otherwise. The external audit : Two measurements for audit quality will be considered in our study; the audit firm reputation (BIG) is proxied using a binary variable that equals to 1 if the firm’s accounts are certified by at least one BIG-4 accounting firm and 0 otherwise.…”
Section: Methodology Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“… POSTREG: The variable of interest post-regulation (POSTREG) is measured by a binary variable which takes value of 1 during the period after the change of regulation and value 0 for the period before – the change of regulation (Cohen et al , 2005, 2008; Lobo and Zhou, 2006, 2009; Naser et al , 2002; El-Gazzar et al , 2009). Board of directors : Three measurements will be considered in our study, namely, size of the board (BSIZE), measured by the number of directors on the board of directors (Yermack, 1996; Adams and Mehran, 2002; Klein, 2002b); the independent director (OUTSD), several researchers have addressed the influence of the percentage of outside director on the board of directors and they found a positive association between the independence of directors and the level of financial disclosure (Bhagat and Black, 1999); and audit committee (ACOM), measured by a dummy variable equal to 1 if the company has an internal audit committee and 0 otherwise. The external audit : Two measurements for audit quality will be considered in our study; the audit firm reputation (BIG) is proxied using a binary variable that equals to 1 if the firm’s accounts are certified by at least one BIG-4 accounting firm and 0 otherwise.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…POSTREG: The variable of interest post-regulation (POSTREG) is measured by a binary variable which takes value of 1 during the period after the change of regulation and value 0 for the period before – the change of regulation (Cohen et al , 2005, 2008; Lobo and Zhou, 2006, 2009; Naser et al , 2002; El-Gazzar et al , 2009).…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…Another important issue is academic researchers may utilise different models to accounts for risk factors and potentially to figure out the optimal estimation laws. Study Jeon ( 2021 ), Markoulis and Neofytou ( 2019 ), Flouris and Walker ( 2005 ), Kolaric and Schiereck ( 2016 ), Gillen and Lall ( 2003 ), Bouoiyour and Selmi ( 2018 ), Krieger and Chen ( 2015 ), Wang ( 2013 ), Rauh and Schneider ( 2013 ), Chen et al ( 2010 ), El-Gazzar et al ( 2009 ), Cam ( 2008 ), da Silva Rocha and Figueiredo Pinto ( 2006 ), Drakos ( 2004 ), Kim and Gu ( 2004 ), Goodrich ( 2002 ), Karels ( 1989 ). Topic area New method to predict share price Methods Component Analysis (PCA), two-stage (operational and stock market indicators) network data envelopment analysis process, the binomial option pricing model, Black-Scholes model, discounted cash flow (DCF) methodology, design a framework to account for acquisition and valuation risks, Multiple Objective Linear Programming (MOLP) optimisation model, integrated approach based on genetic fuzzy systems (GFS) and artificial neural networks (ANN), contingent claims valuation model, the real options framework to develop a multi-stage investment in the aerospace maintenance, repair, and overhaul (MRO) industry Main finding It is claimed that introducing new model can help industry practitioners in figuring-out the profitability potentials.…”
Section: Assessment Of the Selected Publicationsmentioning
confidence: 99%
“…In terms of value relevance, previous studies showed that changes in the accounting standards (Chebaane & Othman 2014;Agostino, Drago & Silipo 2011;Clarkson, Hanna, Richardson & Thompson 2011;Kadri, Abdul Aziz & Ibrahim 2009;Goodwin, Ahmed & Heaney 2008;Bartov, Goldberg & Kim 2005); type of industry (Tan, Hassan & Embong 2014;El-Gazzar, Finn & Tang 2009;Nwaeze 1998) and corporate governance of the firm (Cormier 2014;Jamaluddin, Mastuki & Elmiza Ahmad 2009;Cools & van Praag 2007;Davis-Friday, Eng & Liu 2006) influence value relevance of accounting numbers (book value of equity & earnings). However, none of these studies examined the role of incoming CEOs/MDs on the value relevance of accounting numbers.…”
Section: Introductionmentioning
confidence: 99%